ナンキョクイキ ニオケル チカク ジキ イジョウ ノ コウシテン データ - 渋谷, 和雄; シブヤ, カズオ; 野木, 義史; ノギ, ヨシフミ; 竹中, 潤; タケナカ, ジュン; SHIBUYA, Kazuo; NOGI, Yoshifumi; TAKENAKA, Jun (1995)
P(論文) MAGSAT衛星の三成分フラックスゲート磁力計データを用いて合成された全磁力値から主磁場及びMPDF法により得られる極域擾乱外部磁場を除去した南極域での地殼磁気異常がJ. TAKENAKA et al. (J. Geomagn.Geoelectr., 43,525,1991)によって求められている。我々は彼らの作成した3°×3°メッシュデータをもとに, 1°×1°メッシュの内挿格子点データをGMTプログラムを用いて作成した。そして, これら格子点データをワークステーション上のanonymous ftpサイトに置くことにより, 利用者が自由にアクセスできるように整備した。 Crustal magnetic anomalies in the Antarctic region were obtained by J. TAKENAKA et al. (J.Geomagn. Geoelectr., 43,525,1991) applying the Mean Polar Disturbance Field (MPDF) method. We generated 1°×1°grid data sets from their original 3°×3°mesh data, using the GMT program. These data sets were prepared under an anonymous ftp site of the workstation at the Center for Antarctic Environment Monitoring (CAEM) of the National Institute of Polar Research (TCP/IP address : 133.57.3.2), and made accessible to users. departmental bulletin paper